Evaluation of the reliability of measurements in cephalograms generated from cone beam computed tomography - Silva,Maurício Barbosa Guerra da (2013)
OBJECTIVE: The purpose was to compare angular and linear measurements generated in digital cephalometric radiographs and cephalograms synthesized from three-dimensional images. METHODS: Twenty-six individuals (12 men and 14 women) with mean age of 26.3 years were selected. Digital cephalometric radiographs and CBCTs were taken on the same day. The images were imported and analyzed on Dolphin Imaging V.10.5 software, which synthesized cephalograms in perspective projection and magnification of 9.7%. A single observer marked the points and repeated the procedure with an interval of time of ten days to evaluate intraexaminer error. In the statistical analysis paired Student's t test was used to establish the correlation between the measurements. RESULTS: The angular measurements GoGn.SN and IMPA, which involved the Gonial point (Go) and the linear measurements that involved the lips presented significant difference (p < 0.05). The other measurements presented good correlation. CONCLUSION: The measurements in the synthesized cephalograms proved to be reliable.